Molecular and Functional Characterization of Novel Fructosyltransferases and Invertases from Agave tequilana - Cortés-Romero, Celso; Martínez-Hernández, Aída; Mellado-Mojica, Erika; López, Mercedes G.; Simpson, June (PLOS ONE, 2012)
Fructans are the main storage polysaccharides found in Agave species. The synthesis of these complex carbohydrates relies on the activities of specific fructosyltransferase enzymes closely related to the hydrolytic invertases. Analysis of Agave tequilana transcriptome data led to the identification of ESTs encoding putative fructosyltransferases and invertases. Based on sequence alignments and structure/function relationships, two different genes were predicted to encode 1-SST and 6G-FFT type fructosyltransferases, in addition, 4 genes encoding putative cell wall invertases and 4 genes encoding putative vacuolar invertases were also identified. Probable functions for each gene, were assigned based on conserved amino acid sequences and confirmed for 2 fructosyltransferases and one invertase by analyzing the enzymatic activity of recombinant Agave protein s expressed and purified from Pichia pastoris. The genome organization of the fructosyltransferase/invertase genes, for which the corresponding cDNA contained the complete open reading frame, was found to be well conserved since all genes were shown to carry a 9 bp mini-exon and all showed a similar structure of 8 exons/7 introns with the exception of a cell wall invertase gene which has 7 exons and 6 introns. Fructosyltransferase genes were strongly expressed in the storage organs of the plants, especially in vegetative stages of development and to lower levels in photosynthetic tissues, in contrast to the invertase genes where higher levels of expression were observed in leaf tissues and in mature plants.